Development of a new resisted technique in active drag estimation - Hazrati, P.; Mason, B. R.; Sinclair, P. J.; Sacilotto, G. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
This investigation aimed to develop a new technique for the estimation of active drag in front crawl swimming at the swimmer's maximum swim speed, while allowing for intra stroke velocity fluctuation. This new resisted technique was developed using similar assumptions to that of the Velocity Perturbation Method (VPM) of Kolmogorov & Duplishcheva (1992). The investigation included twelve national and international male swimmers who were asked to perform two maximum effort free swim trials, two passive and two active drag trials. The data required for the calculation of active drag were maximum swim speed, which was derived from the free swim trials, and a force set between 4 to 10 N and which was dependent upon the mean value of passive drag. Mean active drag ranged from 68 to 123.2 N in front crawl. The mean active drag values found in this investigation were in agreement with those previously reported by Kolmogorov & Duplishcheva (1992) and Wang et al. (2007). These three techniques using resisted swimming (VPM, Wang et al. and the current study) provided similar values for mean active drag to one another.